Suppression of the Shastry-Sutherland phase driven by electronic concentration reduction in magnetically frustrated Ce2.15Pd1.95(Sn1-yIny)0.9 alloys - Sereni, J.G.; Roberts, J.; Gastaldo, F.; Giovannini, M.; Sereni, Julián (American Physical Society, 2019)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina